Investigation of papA, papC, and papG virulence genes revealed their association with antimicrobial resistance among uropathogenic Escherichia coli strains isolated from patients in Thi-Qar province, Iraq (Texas Journal of Medical Science, 2023)
Infection of the urinary tract is one of the more common infections in the people of the world, which is more common in women due to the anatomical structure of the woman's body. The main cause of this infection is uropathogenic E. coli, followed by Klebsiella pneumoniae. This disease is controlled and treated by antibiotics, but one of the most important concerns in today's world is the spread of antibiotic resistance in different strains of bacteria. This resistance to antibiotics is caused by specific genes that increase the number of these identified genes every day. This study aims to find the frequency of three coding genes related to p fimbriae, namely papA, papC, and papG, from E. coli strains extracted from patients with urinary tract infections. Also, in this research, by conducting tests related to the detection of the antimicrobial resistance of the extracted strains and using statistical analysis, an attempt has been made to find a significant relationship between the presence or absence of a gene and resistance to antibacterials. At first, 110 urine samples were collected from patients with UTI in the Dhi Qar province of Iraq. In this research, bacterial culture methods in McConkey agar and advanced biochemical tests were used for primary confirmation of E. coli contamination, and Vitek2 and API E20 systems were used for secondary confirmation of bacterial contamination in suspected samples. Finally, the result of these tests was that all 110 samples were infected with E. coli. Then, samples resistant to the antibiotics Ampicillin, Tetracycline, Ciprofloxacin, Nitrofurantoin, and Cotrimoxazole, respectively, were detected by culturing in MuellerHinton agar medium and disc diffusion using the CLSI 2021 protocol. 36.36, 24.54, 29.09, 2.72, and 20% of the samples were resistant to these antibiotics, respectively. PCR was used to amplify gene fragments, and agarose gel electrophoresis was used to determine the presence of genes. The result was that the percentages of papG, papC, and papA genes were 61.81, 38.18, and 28.18, respectively. Finally, by performing a chisquare test in SPSS software, it was found that there is a significant relationship between the presence or absence of papA and papC genes with ampicillin and a significant relationship between papG and cotrimoxazole. These findings and the findings of other researchers can help us choose the right treatment and design new treatments by determining the antibiotic resistance factor